High current gain 4H-SiC bipolar junction transistor*Project supported by the National Natural Science Foundation of China (Nos. 61306093, 61401075). (April 2016) - Zhang 张, Yourun 有润; Shi 施, Jinfei 金飞; Liu 刘, Ying 影; Sun 孙, Chengchun 成春; Guo 郭, Fei 飞; Zhang 张, Bo 波
Abstract: A novel 4H-SiC BJT of high current gain with a suppressing surface traps effect has been proposed. It is effective to improve the current gain due to the lower electrons density in the surface region by extending the emitter metal to overlap the passivation layer on the extrinsic base surface. The electrons trapped in the extrinsic base surface induce the degeneration of SiC BJTs device performance. By modulating the electron recombination rate, the novel structure can increase the current gain to 63.2% compared with conventional ones with the compatible process technology. Optimized sizes are an overlapped metal length of 4 μ m, as well as an oxide layer thickness of 50 nm.